2019
DOI: 10.1002/ptr.6400
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis sativa L. extract and cannabidiol inhibit in vitro mediators of skin inflammation and wound injury

Abstract: Funding informationLinnea SA; Ministero dell'Istruzione, dell'Università e della Ricerca (MIUR), Grant/ Award Number: Progetto Eccellenza-DiSFeB Skin inflammatory diseases result from complex events that include dysregulation and abnormal expression of inflammatory mediators or their receptors in skin cells. The present study investigates the potential effect of a Cannabis sativa L. ethanolic extract standardized in cannabidiol as antiinflammatory agent in the skin, unraveling the molecular mechanisms in human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 34 publications
4
86
0
2
Order By: Relevance
“…To our knowledge, information on the anti-inflammatory effect of hemp EOs is very limited. On the other hand, some authors [45] reported that CBD-enriched extracts can reduce IL-8 and Nf-κB pathways. However, in this study, we demonstrated that the CBD-free hemp EOs did not induce an inflammatory condition, but, additionally, were able to revert an inflammatory condition, reducing the release of the cytokine induced by ETO, on skin cell lines, suggesting that they could be safely used by operators.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, information on the anti-inflammatory effect of hemp EOs is very limited. On the other hand, some authors [45] reported that CBD-enriched extracts can reduce IL-8 and Nf-κB pathways. However, in this study, we demonstrated that the CBD-free hemp EOs did not induce an inflammatory condition, but, additionally, were able to revert an inflammatory condition, reducing the release of the cytokine induced by ETO, on skin cell lines, suggesting that they could be safely used by operators.…”
Section: Discussionmentioning
confidence: 99%
“…To observe the effect of CBD, following irradiation cells were incubated for 24 h in medium containing 4 µM of CBD. Used concentration of CBD did not alter the morphology or proliferation of fibroblasts [14] and cells viability measured by MTT test (data not shown). During this incubation the medium did not contain FBS to avoid the influence on proteomic results.…”
Section: Methodsmentioning
confidence: 99%
“…A study by Sangiovanni et al reported the effects of CBD and Cannabis Sativa Extract (CSE, standardized to 5% CBD) on human keratinocytes (HaCaT cells) and human dermal fibroblast (HDF) cells. 97 In keratinocytes, TNF-α (Tumor Necrosis Factor alpha) treatment resulted in upregulated expression of 26 genes involved in inflammatory pathways and included chemokines like CXCL8 and CXCL10, interleukins like IL−17C and IL−1B, and VEGF-A. Treatment with CSE downregulated all 26 inflammatory related genes, and CBD alone downregulated 15 genes.…”
Section: Wound Healingmentioning
confidence: 99%